Additions to the knowledge on the genus Philanthus Fabricius, 1790 (Hymenoptera: Crabronidae: Philanthinae) from the Indian subcontinent - Kumar, P. Girish; Monks, Joseph; Sheikh, Altaf Hussain (Zootaxa, 2021)
Additional information on the genus Philanthus Fabricius from the Indian subcontinent is provided, with a key to species. Two new synonymies are proposed: Philanthus avidus Bingham, 1896 and P. scrutator Nurse, 1902 are synonymised under P. basalis F. Smith, 1856. P. nepalensis Bingham and P. triangulum Fabricius are reported for the first time from India. The distribution data of P. basalis F. Smith, P. dentatus Cameron, P. depredator F. Smith, P. pulcherrimus F. Smith, and P. ramakrishnae Turner within various states of India are augmented.